Radiotherapy for Tracheal Squamous Cell Carcinoma: A Review - Larnaudie, A.; Orliac, H.; Lerouge, D.; Naessens, C.; Deny, N.; Serre, R.; Clavere, P. (Archives of Clinical and Medical Case Reports, 2022)
Tracheal cancer is a rare localization without official recommendation nether European nor French. This review summarizes the data published about tracheal squamous cell carcinoma treated with radiotherapy in terms of dose and fractionation, techniques, volume, toxicity, overall survival and local control.